Answer

Verified

374.1k+ views

**Hint:**First of all we will take the given expression and take differentiation with respect to “x” and “y” one by one and then find the factors and place the values of one variable to get the value for the other variable.

**Complete step by step solution:**

Take the given expression:

$f(x,y) = {x^3} + xy - {y^3}$

Differentiate the above expression with respect to “x”

\[\dfrac{d}{{dx}}f(x,y) = \dfrac{d}{{dx}}({x^3} + xy - {y^3})\]

Apply differentiation to all the terms on the right hand side of the equation inside the bracket.

\[{f_x} = \dfrac{d}{{dx}}({x^3}) + \dfrac{d}{{dx}}(xy) - \dfrac{d}{{dx}}({y^3})\]

Apply the formula in the above equation and place the value in it.

\[{f_x} = 3{x^2} + y\]

To find the critical value in the above equation equal to zero.

\[0 = 3{x^2} + y\] …. (A)

Similarly take derivative in the given expression with respect to “y”

\[\dfrac{d}{{dy}}f(x,y) = \dfrac{d}{{dy}}({x^3} + xy - {y^3})\]

Apply differentiation to all the terms on the right hand side of the equation inside the bracket.

\[{f_y} = \dfrac{d}{{dy}}({x^3}) + \dfrac{d}{{dy}}(xy) - \dfrac{d}{{dy}}({y^3})\]

Apply the formula in the above equation and place the value in it.

\[{f_y} = x - 3{y^2}\]

To find the critical value in the above equation equal to zero.

\[0 = x - 3{y^2}\] …. (B)

Take equation (A)

\[y = - 3{x^2}\]

Place the above value in the equation (B)

\[x - 3{( - 3{x^2})^2} = 0\]

Simplify the above equation-

\[x - 27{x^4} = 0\]

Finding the factors of the above equation.

$ \Rightarrow x(1 - 27{x^3}) = 0$

Implies

$x = 0$ …. (C)

or $1 - 27{x^3} = 0$

Simplify the above equation:

$1 = 27{x^3}$

When term multiplicative on one side is moved to the opposite side, then it goes to the

denominator.

$ \Rightarrow {x^3} = \dfrac{1}{{27}}$

Take a cube-root on both the sides of the equation.

$ \Rightarrow x = \dfrac{1}{3}$ …. (D)

Using the equation (C) and equation (A)

\[0 = 3{x^2} + y\]

Make “y” the subject, when any term is moved from one side to another the sign of the term also changes.

$y = - 3{x^2}$

Place $x = 0$

$ \Rightarrow y = - 3(0)$

Zero multiplied with anything gives zero.

$ \Rightarrow y = 0$ … (E)

Now, Place $x = \dfrac{1}{3}$ in equation (A)

$ \Rightarrow y = - \dfrac{1}{3}$

**Hence, the critical points are: $(0,0)$ and $\left( {\dfrac{1}{3}, - \dfrac{1}{3}} \right)$**

**Note:**Be careful about the sign convention when doing simplification. When you move any term from one side to another then the sign of the term also changes. Positive terms become negative and vice-versa.

Recently Updated Pages

The base of a right prism is a pentagon whose sides class 10 maths CBSE

A die is thrown Find the probability that the number class 10 maths CBSE

A mans age is six times the age of his son In six years class 10 maths CBSE

A started a business with Rs 21000 and is joined afterwards class 10 maths CBSE

Aasifbhai bought a refrigerator at Rs 10000 After some class 10 maths CBSE

Give a brief history of the mathematician Pythagoras class 10 maths CBSE

Trending doubts

Difference Between Plant Cell and Animal Cell

Give 10 examples for herbs , shrubs , climbers , creepers

Name 10 Living and Non living things class 9 biology CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

Write a letter to the principal requesting him to grant class 10 english CBSE

Fill the blanks with proper collective nouns 1 A of class 10 english CBSE

Write the 6 fundamental rights of India and explain in detail